Exploring potential imaging biomarkers for ischemic retinal vein occlusion: insights from fundus autofluorescence and optical coherence tomography - Wang, Zixun; Zhou, Jun; Hu, Xiaoxue; Ding, Jingjie; Zhang, Xiaoling; Wei, Ruihua; Qin, Xiuhong; Li, Zhiqing (Frontiers in Medicine, 2025)
PurposeThis study aimed to investigate the characteristics of macular edema observed by fundus autofluorescence (FAF) and to analyze noninvasive indicators of ischemia in retinal vein occlusion (RVO) through FAF or optical coherence tomography (OCT). We specifically report a newly recognized FAF–OCT mismatch in ischemic RVO, in which CME is not detectable on FAF.MethodsThis study included 74 participants. 49 eyes of 49 patients with RVO and 25 healthy control eyes were included in the study. All patients underwent a complete ophthalmologic examination and were evaluated with FAF, fundus fluorescein angiography (FFA), and OCT. The optical intensities of the inner and outer retinal layers were measured using ImageJ software.ResultsOf 49 eyes in RVO patients, FAF imaging showed typical Cystoid macular edema (CME) with hyperautofluorescence in non-ischemic RVO patients (69.57%) and in ischemic RVO patients (26.92%, p = 0.029, p < 0.05). Disorganization of retinal inner layers (DRIL) was observed in 13 eyes in the non-ischemic RVO group and 23 eyes in the ischemic RVO group. (χ 2= 6.387, p = 0.012, p < 0.05) The prominent middle-limiting membrane (p-MLM) sign was found in 5 eyes in the non-ischemic RVO group and 15 eyes in the ischemic RVO group. (χ 2= 6.530, p = 0.011, p < 0.05) The mean optical intensity of the retinal pigment epithelium (RPE) layer, ellipsoid, and interdigitation zones in the ischemic RVO group was 109.78 ± 19.327, which was significantly lower compared to the non-ischemic RVO group (172.31 ± 30.527, p = 0.001, p < 0.01).ConclusionCME in patients with ischemic RVO is less easily detectable on FAF compared to patients with non-ischemic RVO. This lack of correspondence may provide insight into the type of RVO. We conclude that the presence of DRIL, a p-MLM sign, impairment of the integrity of the external limiting membrane (ELM), and decreased optical intensity or integrity of the ellipsoid zone and RPE can serve as effective indicators of ischemia in RVO patients.